SYNTHESIS OF TRANSITION METAL OXIDE NANOCRYSTALS BY COST EFFECTIVE HYDROTHERMAL PROCESS - Durrani, S. K.; Khan, Y.; Khan, M. R.; Haq, M. A. (The Nucleus, 2020)
Simple and cost effective hydrothermal process was used for synthesis of nanocrystals of transition metal oxides such as manganese oxide (α-MnO2), nickel oxide (NiO) and zinc oxide (ZnO). These nanocrystals were synthesized through hydrothermal decomposition under autogenous pressure condition using metal nitrates and ammonium hydroxide salts in aqueous solutions. The percent yield of synthesized selective oxide products was very good at pH values (> 3.2-3.5 for α-MnO2 and 9-9.6 for NiO and ZnO) irrespective of the solvent composition. The synthesized products were characterized by X-ray diffraction (XRD), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM) and Brunauer-Emmet-Teller analysis (BET). The XRD results indicated that the synthesized MnO2, NiO and ZnO had body centered tetragonal, cubic and wurtzite structures having crystalline size 68±0.74, 33±0.14 and 54±0.38 nm respectively. However, the average crystalline sizes derived from BET method were found higher than XRD values indicated the agglomeration of nanocrystals. SEM analysis revealed the thickness of MnO2 nanowires and NiO nanobelts were in range of 50-90nm and 20-40nm respectively whereas the diameter of ZnO nanorods was about 80- 200nm and lengths of over 8-12μm.